Integrated profiling identifies NCOA3 as a prognostic factor in patients with glioma - Qian Luo; Jiaying Yang; Hailin Yin; Mei Yang; Yueyang Liang; Yixuan Hou; Xinze Sun; Jixuan Liu; Ling Zhang (Functional & Integrative Genomics, 2026)

Parameter sensitivity and inversion errors in a leaky aquifer system: the impact of neglecting aquitard nonlinear consolidation - Xianmeng Meng; Xiaoxuan Liu; Wenjuan Zhang; Qu Wang; Maosheng Yin; Dengfeng Liu (Advances in Water Resources, 2026)

Multi-scale propagation of meteorological to agricultural drought across China: probabilities and dominant drivers - Xinxuan Li; Chongli Di; Hanqiong Zhang; Haijiang Wu (Theoretical and Applied Climatology, 2026)

MDAGCN: A multimodal dynamic adaptive graph convolutional network for sleep staging - Dongsheng Fang; Chu Li; Haoxuan Li; Xiaodong Yang (Medical & Biological Engineering & Computing, 2026)

A study on eye movement trajectory classification for strabismus screening via integration of global dependencies and temporal dynamics - Zhuo Liang; Zihe Zhao; Enci Xie; Yuxuan Liu; Boxin Yao; Chenyu Tang; Shuo Gao (Medical & Biological Engineering & Computing, 2026)

Dimethyl trisulfide inhibits Alternaria alternata by disrupting reactive oxygen species (ROS) homeostasis and energy metabolism - Huan Qu; Ershuai Yang; Zongze Li; Yaoxuan Li (European Journal of Plant Pathology, 2026)

Amino acid-chelated zinc application enhances sugar beet growth performance in carbonate alkaline soil by optimizing rhizosphere zinc speciation and microbial community structure - Jianyu Zhang; Chuanhe Zhao; Yunlong Guo; Muhammad Ishfaq; Songlin Yang; Wenya Wang; Qiue Jia; Shangxuan Liu; Yan Wang; Wang Xing; Baiquan Song (Applied Soil Ecology, 2026)

Intergeneric hybridization of Chanodichthys erythropterus (♀) and Culter alburnus (♂) generates fertile diploid hybrids - Xu Huang; Xiaoyu Huang; Jian Li; Jiaxuan Zhu; Jiawang Huang; Can Xu; Lang Qin; Yingying Yang; Hongxuan Liang; Yuxiang Wang; Fangzhou Hu; Chang Wu; et al. (Aquaculture, 2026)

Varietal traits of Lycium barbarum cultivars structure rhizosphere microbial communities and influence root rot susceptibility - Chenbo Jia; Shuxuan Liu; Jianyu Su; Chunyan Xu (Applied Soil Ecology, 2026)

Metagenomic insights into the influence of rhizosphere microbiome functional profiles for soil phosphorus mobilization under Pseudomonas combinations and phosphate addition - Xiaolei Yang; Qi Li; Changning Li; Xinrui Xu; Yaxuan Liu; Kerui Wu; Tuo Yao (Applied Soil Ecology, 2026)

Emerging Viruses in Decapod Crustaceans: A Global Review - Xuan Dong; Guohao Wang; Kejun Wang; Kaisong Zhang; Hua Xu; Liying Wang; Xuan Li; Liang Qiu; Win Surachetpong; Jing Wang; Jee Eun Han; Kathy F. J. Tang; et al. (Reviews in Aquaculture, 2026)
Due to its advantages of a short production cycle, wide market demand, and profitability, decapod crustacean aquaculture has become one of the fastest‐growing food production systems. However, disease outbreaks have become one of the most important factors limiting the sustainability of decapod crustaceans. This review synthesizes current advancements in the understanding of emerging viral pathogens in decapod crustacean aquaculture, with emphasis on their genomic‐based taxonomical classification, susceptible hosts, global distribution, clinical manifestations, pathogenic mechanisms, diagnostic developments, and management strategies. This paper summarizes details of emerging viruses with confirmed pathogenicity (such as decapod iridescent virus 1), as well as viruses with uncertain or yet‐unconfirmed pathogenic roles. In addition, we highlight the role of next‐generation sequencing in virus discovery and examine the challenges posed by coinfection with other microorganisms. This review provides information to help the decapod crustacean aquaculture industry in setting up early warning systems to prevent the introduction of emerging pathogens into the production systems.

Exacerbation of microbial phosphorus limitation in cadmium-contaminated soil under maize-rape rotation - Jiaxin Chen; Jieyi Yu; Tingxuan Li; Huagang Huang; Keji Wang; Lu Zhang; Daihua Ye; Xizhou Zhang; Yongdong Wang; Tao Liu; Haiying Yu (Applied Soil Ecology, 2026)

One-dimensional non-Darcian flow model incorporating the impact of nonlinear clay consolidation on the threshold hydraulic gradient - Xianmeng Meng; Lintao Shen; Xiaoxuan Liu; Qu Wang; Maosheng Yin; Dengfeng Liu (Advances in Water Resources, 2026)

Differences in temporal patterns of bacterial community assembly between soybean rhizosphere and endosphere - Ting Jin; Shuanghui Wang; Yong Wu; Junyao Deng; Xuanjing Li; Yao Liu; Jianli Zhang; Wuxuan Li; Gehong Wei; Peng Shi (Applied Soil Ecology, 2025)

Soil microbial community harboring key genes drives rhizosphere phosphorus mobilization of phosphorus-accumulating Polygonum hydropiper - Daihua Ye; Yuyue Lin; Tao Liu; Xizhou Zhang; Yu Tang; Keji Wang; Huagang Huang; Haiying Yu; Yongdong Wang; Xinhua He; Tingxuan Li (Applied Soil Ecology, 2025)

Niche differentiation shapes the community assembly of fungi associated with evergreen trees in the Horqin desert - Xuan Liu; Pei-shan Zhao; Guang-lei Gao; Yue Ren; Guo-dong Ding; Ying Zhang (Applied Soil Ecology, 2024)

Nitrogen application enhanced phosphorus-phytoextraction of Polygonum hydropiper from high phosphorus soil in relation to rhizosphere phosphorus fractions - Min Xie; Daihua Ye; Yu Guo; Xizhou Zhang; Tao Liu; Huagang Huang; Haiying Yu; Yongdong Wang; Yu Tang; Zicheng Zheng; Tingxuan Li (Applied Soil Ecology, 2024)

Erratum to: Discriminating Dabry’s sturgeon (Acipenser dabryanus) and Chinese sturgeon (A. sinensis) based on DNA barcode and six nuclear markers - Jiuxuan Li; Dongqi Liu; Qingzhan Ma; Xiuyue Zhang; Wei Dai; Yongbo Chen; Yong Liu; Zhaobin Song (Hydrobiologia, 2015)

Discriminating Dabry’s sturgeon (Acipenser dabryanus) and Chinese sturgeon (A. sinensis) based on DNA barcode and six nuclear markers - Jiuxuan Li; Dongqi Liu; Qingzhan Ma; Xiuyue Zhang; Wei Dai; Yongbo Chen; Yong Liu; Zhaobin Song (Hydrobiologia, 2015)